2021
DOI: 10.1016/j.jhep.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Management of bacterial and fungal infections in cirrhosis: The MDRO challenge

Abstract: Bacterial infections are frequent in cirrhotic patients with acute decompensation or acute-on-chronic liver failure and can complicate the clinical course. Delayed diagnosis and inappropriate empirical treatments are associated with poor prognosis and increased mortality. Fungal infections are much less frequent, usually nosocomial and associated with extremely high short-term mortality. Early diagnosis and adequate empirical treatment of infections is therefore key in the management of these patients. In rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 110 publications
(216 reference statements)
0
119
0
4
Order By: Relevance
“…Our data suggested that HpeI-encoding Enterobacterales increased in the gut of the patients with LC. Other studies showed that E. coli , Klebsiella pneumoniae , and other Enterobacterales are the most common and are responsible for up to 50% in patients with cirrhosis ( Fernández et al, 2021 ). While both bacteria from Enterobacterales and Burkholderiales increased in the gut of CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that HpeI-encoding Enterobacterales increased in the gut of the patients with LC. Other studies showed that E. coli , Klebsiella pneumoniae , and other Enterobacterales are the most common and are responsible for up to 50% in patients with cirrhosis ( Fernández et al, 2021 ). While both bacteria from Enterobacterales and Burkholderiales increased in the gut of CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, AMR has become a significant global problem in patients with cirrhosis. 4 A large US study found that patients with cirrhosis' risk of dying from sepsis increased by 28% between 2002 and 2010, 5 and it has been proposed that this may be related to the increasing spread of multidrug-resistant organisms (MDROs). 6…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…17,18 The prevalence of bacterial infections in patients with cirrhosis is 5-6 times that of the general population. 4…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these addresses the challenge of infection with multidrug resistant organisms. 8 The novel concept of disease modifying approaches to the treatment of cirrhosis as an unmet need is discussed in the next chapter. 9 The following chapter deals with the very common scenario where the clinical team is working beyond clinical guidelines to try and save the lives of the patients with decompensated cirrhosis.…”
mentioning
confidence: 99%